Anchorage of composite dowels in UHPC under fatigue loading. (17th May 2016) - Classen, Martin; Gallwoszus, Joerg; Stark, Alexander
Abstract: In steel‐concrete composite structures, innovative composite dowels can be used for the connection of ultra‐high‐performance concrete (UHPC) slabs and high‐strength steel members. In addition to sufficient shear capacity, composite dowels have to ensure the transmission of tensile forces in the composite connection in order to prevent lifting of the concrete slab. This may lead to structural problems, particularly in the very slender concrete slabs of high‐strength composite beams, where composite dowels have very small embedment depths. Although findings concerning the structural anchorage behaviour of composite dowels under static loads are already available, studies on the fatigue of composite dowels under cyclic pull‐out loading are still lacking. As fatigue behaviour is crucial for applications in bridge construction, the present paper introduces cyclic pull‐out tests on composite dowels in UHPC slabs in which the influence of different load‐dependent parameters (upper load level and load range) as well as the use of transverse reinforcement has been investigated. Furthermore, an approach to assess the lifetime of composite dowels in UHPC under cyclic pull‐out loading is proposed.